Señoríos y heredades de Íñigo López de Orozco en los concejos de Atienza, Medinaceli y Molina de Aragón - Ávila Seoane, Nicolás (En la España Medieval, 2006)
A detailed study of the origin and transmission of the jurisdictional lordships and patrimonial properties of Íñigo López de Orozco during the reigns of Alfonso XI and Peter I of Castile in the “lands” of Atienza, Medinaceli and Molina. Their diverse destiny upon the titleholder’s death and the division of the inheritance among his four daughters. The acquisitions of Pedro González de Mendoza. Includes documents, a genealogical table and maps.